PENGATURAN BUNGA PINJAMAN DALAM LAYANAN TEKNOLOGI FINANSIAL JENIS PEER TO PEER LENDING - Rahyuni Septiana, Ni Luh Gede Dini; Gde Rudy, Dewa (Kertha Semaya : Journal Ilmu Hukum; Vol 8 No 6 (2020), 2020)
The purpose of this article is to know and understand loan interest arrangements on Financial Technology services, the type of peer to peer lending (P2P lending) services and OJK's responsibility in regulating and overseeing the implementation of P2P lending services. The method used is normative legal research. The conclusions of this paper show that in P2P lending services it is inseparable from the imposition of interest on loans which is one of the requirements in electronic documents as determined by the parties. In its determination, loan interest is based on the agreement between the lender and the loan recipient based on the recipient of the approval on the basis of an agreement on the fairness and financial development on a national basis. Regulations imposed by the OJK as an institution that require regulation and supervision in the financial services sector are currently based on the OJK Regulation No. 77 / POJK.01 / 2016 about Information Technology-Based Money Lending and Borrowing Services have not provided a clarity regarding the regulation of loan interest on P2P lending services precisely in terms of loan interest limits. The efforts taken by OJK are in the form of preventive and repressive efforts towards the implementation of P2P lending services. OJK stipulates indirect regulations regarding the maximum amount of lending interest in P2P lending services through the AFPI code of ethics.   Key Words: Financial Technology, Lending Interest Arrangement, P2P Lending, OJK